“On an Island Alone”: The Mental Health and Well-Being of Swimming Coaches in the United Kingdom - Ella McLoughlin; Laura Healy; Julie Johnston; Joseph Stanford (The Sport Psychologist, 2026)
This project examined the mental health and well-being of swimming coaches in the United Kingdom. We explored the impact of workplace stressors and the satisfaction or thwarting of coaches’ basic psychological needs on mental ill-health, well-being, and burnout. Using a mixed-method design, 146 coaches across competitive levels completed an online questionnaire assessing symptoms of mental ill-health, well-being, burnout, stressors, and basic psychological needs and open-ended questions about their coaching experiences. Workload and (a lack of) work–life balance, feeling isolated, undermined, perceiving a lack of support, and the satisfaction or thwarting of basic psychological needs were key drivers for coaches’ symptoms of mental ill-health, well-being, and burnout. Coaches had limited awareness of support services. Findings highlight the need for multilevel interventions: at an individual level, improved mental health education, coping resources, and access to services; and at an organizational level, strategies to ensure manageable workloads and identify and support coaches at risk.